THE DEVELOPMENT OF CONTEXTUAL-BASED UNO STACKO LEARNING MEDIA IN THE THEMATIC LEARNING OF CLASS IV SD NEGERI 11 LUBUKLINGGAU - Nadiya, Chika Rizki; Aswarliansyah, Aswarliansyah; Valen, Andri (Widyagogik, 2022)
This study aims to develop a contextual-based Uno Stacko learning media design for valid, practical, and effective thematic learning. The subjects in this study were2 lecturers as media validators and language validators, class teachers, and 19 class IV.B students at SD Negeri 11 Lubuklinggau. The method used is Research and Development (RD) with a 4-D model, namely define, design, develop, and disseminate. The results of the assessment analysis of all validators obtained a score of 0.85 in the very valid category. Recapitulation of practicality percentage reached96.2%in the very practical category. Then the results of the effectiveness obtained an N-gain value of 0.8 in the high category. It can be concluded that the contextual-based Uno Stacko media is valid, practical, and effective. Thus, it can be stated that Contextual-based Uno Stacko media is suitable for use in thematic learning of fourth grade elementary school students.